2021
DOI: 10.1155/2021/5568159
|View full text |Cite
|
Sign up to set email alerts
|

Effect of GLP-1/GLP-1R on the Polarization of Macrophages in the Occurrence and Development of Atherosclerosis

Abstract: Aims. To investigate the effect of GLP-1/GLP-1R on the polarization of macrophages in the occurrence and development of atherosclerosis. Methods. Totally, 49 patients with coronary heart disease (CHD) and 52 cases of health control (HC) were recruited, all subjects accept coronary angiography gold standard inspection. One or more major coronary arteries (LM, LAD, LCx, and RCA) stenosis degree in 50% of patients as CHD group; the rest of the stenosis less than 50% or not seen obvious stenosis are assigned to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…We conclude that the hotspots of macrophage polarization in AS initially focused on its impact on obesity. Studies explored more critical targets in this area, including Nrf2 ( 59 ), Kruppel-like factor 4 ( 60 63 ), GLP-1/GLP-1R ( 64 ), TLR4 ( 27 , 65 ), and micro RNA ( 66 , 67 ), related to inflammation process and plaque progression. Cardiovascular disease studies, including the role of macrophage polarization in lipid metabolism, inflammatory immune response in plaques, and cerebrovascular disease, are two diseases involved in this field.…”
Section: Discussionmentioning
confidence: 99%
“…We conclude that the hotspots of macrophage polarization in AS initially focused on its impact on obesity. Studies explored more critical targets in this area, including Nrf2 ( 59 ), Kruppel-like factor 4 ( 60 63 ), GLP-1/GLP-1R ( 64 ), TLR4 ( 27 , 65 ), and micro RNA ( 66 , 67 ), related to inflammation process and plaque progression. Cardiovascular disease studies, including the role of macrophage polarization in lipid metabolism, inflammatory immune response in plaques, and cerebrovascular disease, are two diseases involved in this field.…”
Section: Discussionmentioning
confidence: 99%
“…These effects are attributed partly to the glycemic control, weight loss, and subsequent reduction in total cholesterol and triglycerides produced by GLP-1 RAs and also to their anti-inflammatory properties. The latter are related to an inhibition of the expression of pro-inflammatory mediators, such as chemokines and cytokines, as well as a suppression of oxidative stress and endothelium dysfunction, inhibition of monocyte/macrophage infiltration and adhesion, macrophage polarization towards M2, and an inhibition of macrophage transformation to foam cells, all leading to improved plaque stability and impeding plaque progression ( Figure 1 ) [ 159 , 160 , 162 , 163 , 164 , 168 , 169 , 170 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent clinical study performed by Yang et al (2021) separated the beneficial CV effect of GLP-1 RAs in terms of atherosclerosis progression from their hypoglycemic effect in patients with coronary heart disease (CHD), indicating that their role is associated with the polarization of macrophages towards M2, i.e., the anti-inflammatory type ( Figure 2 ) [ 159 ]. The anti-inflammatory effect of liraglutide has also been previously reported from preclinical studies [ 160 ].…”
Section: Explaining the Effectiveness Of Incretin-based Drugs On Nash...mentioning
confidence: 99%
“…TZDs treatment could attenuate Diabetes is a major risk factor for coronary heart disease (27), and the mortality rate of coronary heart disease is higher in diabetic patients than in non-diabetic subjects (28). Studies have shown that diabetic patients with concomitant coronary atherosclerosis have more extensive and severe coronary artery lesions (29), which may be associated with disorders of glucose metabolism, disorders of lipid metabolism, inflammatory response, and endothelial damage (30)(31)(32).…”
Section: Discussionmentioning
confidence: 99%